An Audit on Substance Misuse Screening and Documentation in Acute Inpatient General Psychiatry Ward - Ariana Axiaq; Ly Bui Dieu; Joseph Itimi (BJPsych Open)
Aims: Scotland has the highest drug-related death rate in Europe, with 27.7 deaths per 100,000 people. The average age of drug-related deaths in Scotland has increased from 32 in 2000 to 44 in 2021, with a significant proportion involving multiple substances. According to NICE and Scottish Intercollegiate Guidelines Network (SIGN) guidelines, best practice management for inpatients with co-occurring substance misuse and mental health should involve: Screening and Identification of Substance Misuse, Integrated Dual Diagnosis Care, Pharmacological and Psychosocial Interventions, Harm Reduction Approaches in Acute Psychiatric Wards and Safe Discharge and Aftercare Planning. We have designed a closed-audit loop which has evolved into a quality improvement project to enhance the identification, management, and follow-up care of substance misuse among inpatients in general psychiatry ward at St John’s Hospital, Livingston, Scotland. This project seeks to achieve an 80% compliance rate in substance use assessments, implement standardized protocols for managing active substance misuse, and develop a policy for handling patients under the influence, in possession, or distributing substances by December 2025. Data presented in this abstract is for the closed-loop audit part of a larger quality improvement project.